Afrikaans se unieke posisie en uitdagings in ’n veeltalige Suid- Afrika - Slippers, Jana; Grobler, Anské; van Heerden, Neels (Acta Academica: Critical views on society, culture and politics, 2010)
Afrikaans, as one of the 11 official languages of South Africa, finds itself in a unique position, facing many challenges. This overview of the history and events that lead to this position endeavours to gain insight into the current position of Afrikaans. Currently the literature lacks such an updated contribution. It appears that the challenges of a multilingual South-Africa are not new or unique to Afrikaans, except for the consequences of apartheid. Despite this legacy, Afrikaans can make a significant contribution to the further development of a multilingual South Africa. Research into the day-to-day experience of Afrikaans-speaking people in a multilingual South Africa is needed to exploit this potential.